PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN EKUITAS MEREK TERHADAP KEPUASAN PELANGGAN DI CAFÉ BERINGIN PREMIUM KOTA BATAM - Alvian Laia; Sunargo Sunargo (Universitas Boyolali, 2022)
This study aims to determine the effect of product quality, service quality and brand equity simultaneously and partially on customer satisfaction at Café Beringin Batam City. The method of collecting data is through a questionnaire survey with a sample of 130 respondents. The analytical method used is multiple regression analysis and the type of research used in this study is a survey method. The results obtained on the product quality variable on customer satisfaction with a value of T count > T table (2.751 > 1.656) with a significant level (0.007 < 0.05) so it can be concluded that product quality has a significant influence on customer satisfaction. The service quality variable on customer satisfaction has a T count > T table (5.072 > 1.656) with a significant level (0.000 < 0.05) which means that service quality has a significant effect on customer satisfaction. The results of the research on the Brand Equity variable on customer satisfaction have a T count < T table (1.503 < 1.656) with a significant level (0.135 > 0.05), so it can be concluded that brand equity has no significant effect on customer satisfaction. Meanwhile, the value of f arithmetic > f table can be obtained simultaneously and Sig 0.000 < 0.05. Thus it can be concluded that Ho is rejected and Ha is accepted or in other words the variables of product quality, service quality and brand equity simultaneously have a significant effect on customer satisfaction with an R square value of 0.248, meaning that it shows that the product quality, service quality and brand equity variables can explain the variable customer satisfaction is 24.8%, while 75.2% is explained by other variables not discussed in this study.